In Silico ADME Prediction: Data Sets and Models - Colmenarejo, Gonzalo (Current Computer - Aided Drug Design, 2005)
The models available in the literature for the in silico prediction of ADME (absorption, distribution, metabolism, excretion) properties, as well as the data sets used to derive them, are reviewed. Special emphasis is given to describe the latest and most complete models, with the largest and most diverse data sets. Models for human intestinal absorption, oral bioavailability, plasma protein binding, blood-brain barrier permeation, Pglycoprotein substrates and inhibitors, and metabolism are reviewed and discussed. An attempt is made to describe the general picture emerging from each set of models when possible, as well as the issues remaining to address in the different areas for future work. These models are an example of the utility of models and computer simulations for the prediction of pharmacokinetics.
Keywords: human intestinal absorption